Qur'anic Pedagogy and Critical Thinking: Bridging Revelation and Modern Educational Philosophy - Ahmad Nilnal Munachifdlil Ula; Krisnanda; Muhammad Teguh Kuncoro; Ahmad Mukhlisin (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study explores the relationship between Qur’anic pedagogy and critical thinking in the context of modern educational philosophy. It focuses on how concepts of thinking found in the Qur’an can be understood in relation to contemporary critical thinking skills and how both can be brought together in learning practices. The study uses a qualitative approach with a conceptual, library-based design, drawing on classical Islamic scholarship as well as recent educational literature.The findings indicate that the Qur’an introduces various forms of intellectual engagement such as tafakkur, tadabbur, ta‘aqqul, nazar, and tafaqquh. These concepts reflect processes that are closely related to interpretation, analysis, evaluation, inference, and reflection in modern critical thinking frameworks. In addition, the study proposes an integrative perspective that connects these Qur’anic concepts with student-centered and inquiry-based learning approaches. The study argues that Qur’anic pedagogy is not in opposition to modern educational thought, but can enrich it by adding ethical and spiritual dimensions. It concludes that integrating both perspectives offers a more balanced approach to education, although further empirical studies are needed to examine its application in classroom settings.